Biphasic effects of statins on neuron cell functions under oxygen–glucose deprivation and normal culturing conditions via different mechanisms. Issue 5 (27th August 2022) - Wang, Hui; Chen, Yun; Li, Ping; Chen, Yan; Yu, Danfang; Tan, Qian; Liu, Xiaoli; Guo, Zhenli
Abstract: While there is a growing interest in the use of statins, HMG‐CoA reductase inhibitors, to treat neurodegenerative diseases, statins are associated with conflicting effects within the central nervous system (CNS) without clear evidence of the underlying mechanisms. This study systematically investigated effects of four statins (atorvastatin, pitavastatin, cerivastatin, and lovastatin) on neuronal cells under pathological condition using an in vitro model depicting ischemic injury, as well as tested under physiological condition. All four statins at micromolar concentrations display toxic effects on neuron cells under physiological condition. Atorvastatin and cerivastatin but not pitavastatin or lovastatin at nanomolar concentrations display protective effects on neuron cells under ischemic injury condition, via decreased ischemic injury‐induced oxidative stress, oxidative damage, and inflammation. Mechanistically, atorvastatin, pitavastatin, and lovastatin induces neuron cell apoptosis via prenylation‐independent manner. Other mechanisms are involved in the pro‐apoptotic effect of cerivastatin. Prenylation is not involved in the protective effects of statins under ischemic injury condition. Our work provides better understanding on the multiple differential effects of statins on neuron cells under physiological condition and ischemic injury, and elucidate their underlying mechanisms, which may be of relevance to the influence of statins in CNS. Abstract : This study revealed the multiple differential effects of four statins (atorvastatin, pitavastatin, cerivastatin and lovastatin) on neuron cells under pathological and physiological conditions, and their underlying mechanisms, which may be of relevance to the influence of statins in central nervous system.